Integrating fluorescent nanodiamonds into polymeric microstructures fabricated by two-photon polymerization. - Couto, Filipe Assis (2023)
Nitrogen-vacancy (NV) and other color centers in diamond have attracted much attention as non-photobleaching quantum emitters and quantum sensors. Since microfabrication in bulk dia monds is technically difficult, embedding nanodiamonds with color centers into designed structures is a way to integrate these quantum emitters into photonic devices. In this study, we demonstrate a method to incorporate fluorescent nanodiamonds into engineered microstructures using two-photon polymerization (2PP). We studied the optimal concentration of nanodiamonds in the photoresist to achieve structures with at least one fluorescent NV center and good structural and optical quality. Fluorescence and Raman spectroscopy measurements were used to confirm the presence and location of the nanodiamonds, while absorbance measurements assessed scattering losses at higher concentra tions. Our results show the feasibility of fabricating microstructures embedded within fluorescent nanodiamonds via 2PP for photonics and quantum technology applications.